2018
DOI: 10.1007/s11069-018-3371-3
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability and participation in disaster recovery decisions: public housing in Galveston after Hurricane Ike

Abstract: Hurricane Ike caused massive damages to Galveston Island's residential structures including four public housing developments in September 2008. These developments were located in neighborhoods with some of the lowest incomes and highest percentages of people of color on the Island. Four months later the Galveston Housing Authority (GHA) decided to demolish all four developments consisting of 569 housing units due to the damages to the buildings. Today, despite federal regulations requiring reconstruction, cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…Therefore, public engagement outreach strategies after the disaster should include a wide geographic range where displaced residents would be staying temporarily. Other research has also shown that disparities in displacement and other recovery challenges persist months or even years after the disaster Hamideh and Rongerude 2018;Dash et al 1997); therefore, support to engage the displaced must be provided over a longer period by maintaining contact with these residents and advocacy groups that serve them by using online platforms along with in-person and representative engagement methods.…”
Section: Discussion: Lessons For Participatory Recovery Planningmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, public engagement outreach strategies after the disaster should include a wide geographic range where displaced residents would be staying temporarily. Other research has also shown that disparities in displacement and other recovery challenges persist months or even years after the disaster Hamideh and Rongerude 2018;Dash et al 1997); therefore, support to engage the displaced must be provided over a longer period by maintaining contact with these residents and advocacy groups that serve them by using online platforms along with in-person and representative engagement methods.…”
Section: Discussion: Lessons For Participatory Recovery Planningmentioning
confidence: 99%
“…For example, while engagement of various stakeholders in recovery would increase the opportunities to build resilience (Crawford et al 2013), one of the challenges of ensuring diversity in participatory recovery planning is engaging marginalized groups in the same conversations with powerful stakeholders. Disadvantaged communities have limited access to political power before disasters and often face even more significant barriers to participating in public recovery dialogues in the aftermath (Hamideh and Rongerude 2018). When compared to their more affluent neighbors, low-income households face greater rates of post-disaster displacement (Fothergill and Peek 2004).…”
Section: Effective Participatory Recovery Planning: Challenges and Knmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Peacock and Girard ( 1997 ) assert that economically and socially disadvantaged individuals are more likely to reside in housing that is substandard and are at a greater risk of being damaged from a disaster event. Hamideh and Rongerude ( 2018 ) cite income as a determinant of an individual’s level of participation in post-disaster recovery decision making. Building off of that insight, Ogie and Pradhan ( 2019 ) describe the multiple dimensions of social vulnerability that are influenced by the income factor.…”
Section: Introductionmentioning
confidence: 99%